2022
DOI: 10.1097/nne.0000000000001316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microlectures on Nursing Students' Understanding of Key Medication Administration Concepts

Abstract: Background: Microlectures comprise short audio or video presentations designed to provide a concise explanation of key concepts or topics. Purpose:The study aimed to develop a microlecture module for a nursing course in medication administration and test whether it could improve learning. Methods: The study had a quasi-experimental design. Four classes of sophomore nursing students were divided into the treatment (n = 109) and control groups (n = 84). Pretests, posttests, integrated examinations, and simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…The combination of short videos and nursing theoretical knowledge teaching improves nursing students' understanding of theoretical knowledge. Studies have shown [13] that in the comparison of micro-lecture video teaching methods and traditional online teaching methods, the experimental group's theoretical assessment scores were significantly better than the control group's assessment scores (P < 0.01), and the students had positive feedback about the micro-lecture video teaching methods. Yin [26] decomposed the movements of the closed peripheral infusion method, and the students selected some of the movements by themselves and made a 15-second Douyin short video.…”
Section: The Effects Of Short Videos On Nursing Education 41 Improvem...mentioning
confidence: 98%
See 1 more Smart Citation
“…The combination of short videos and nursing theoretical knowledge teaching improves nursing students' understanding of theoretical knowledge. Studies have shown [13] that in the comparison of micro-lecture video teaching methods and traditional online teaching methods, the experimental group's theoretical assessment scores were significantly better than the control group's assessment scores (P < 0.01), and the students had positive feedback about the micro-lecture video teaching methods. Yin [26] decomposed the movements of the closed peripheral infusion method, and the students selected some of the movements by themselves and made a 15-second Douyin short video.…”
Section: The Effects Of Short Videos On Nursing Education 41 Improvem...mentioning
confidence: 98%
“…Yu and Fang [13] utilized short audio and video presentations to provide concise explanations of medication concepts or topics, and randomly grouped sophomore nursing students into an experimental group that was intervened with a "micro-lecture video + SPS" and a control group that only used traditional online teaching methods. Holland et al [14] investigated the intervention group that received only standard instruction and unlimited access to short videos of practice examples of oral medications, and a control group that received only standard instruction, with learning outcomes assessed by modules and satisfaction questionnaires returned at the end of the class to measure the effectiveness of the instruction.…”
Section: Teaching Nursing Theoretical Knowledgementioning
confidence: 99%